2012
DOI: 10.3174/ajnr.a2966
|View full text |Cite
|
Sign up to set email alerts
|

Common and Expected Postmortem CT Observations Involving the Brain: Mimics of Antemortem Pathology

Abstract: BACKGROUND AND PURPOSE: Postmortem imaging with CT or MR is emerging as an effective technique to augment forensic autopsy. Expected findings on postmortem imaging of the brain may mimic pathologic processes in the living brain, leading to potential misdiagnosis. The purpose of this study is to describe the array of CT findings that can be expected to be present within the brain after death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 7 publications
(8 reference statements)
1
21
0
Order By: Relevance
“…However, we hypothesize that the control group cases in our study exhibited milder brain swelling because reperfusion was absent or limited to the agonal stage. Another factor associated with brain swelling is autolysis, which becomes obvious at 24 h after death [10,13]. We observed two cases with 19-and 30-day intervals between the hypoxic event and death who exhibited pathological findings indicating the so-called respirator brain, which is characterized by autolytic changes [14,15].…”
Section: Discussionmentioning
confidence: 96%
“…However, we hypothesize that the control group cases in our study exhibited milder brain swelling because reperfusion was absent or limited to the agonal stage. Another factor associated with brain swelling is autolysis, which becomes obvious at 24 h after death [10,13]. We observed two cases with 19-and 30-day intervals between the hypoxic event and death who exhibited pathological findings indicating the so-called respirator brain, which is characterized by autolytic changes [14,15].…”
Section: Discussionmentioning
confidence: 96%
“…Brain swelling and a loss of distinction between the gray matter (GM) and white matter (WM) are normal postmortem changes on postmortem CT. Takahashi et al ( 27 ) reported that postmortem brain autolysis may occur without concurrent vasogenic edema owing to hyperacute global ischemia in the absence of reperfusion; as a result, a subtle loss of distinction between the GM and WM can be detected on early postmortem CT. The ventricles and cisterns are sometimes visibly effaced because of mild swelling during the immediate postmortem period ( 27 28 ). The GM and WM densities are considerably higher on postmortem CT than on AMCT, which reflects the presence of severe hypoxic-anoxic encephalopathy before death.…”
Section: Gross Postmortem Ct Images Of the Brainmentioning
confidence: 99%
“…On the other hand, radiologists have to be trained to think 'forensically' , as the interpretation of postmortem findings in the forensic setting is not the same as in clinical practice (Smith et al 2012). Radiologists should learn basic forensic principles.…”
Section: Sample Structure Of the Reportmentioning
confidence: 99%
“…Figures 9.4 and 9.5 show some of the normal PMCT characteristic images which should not be confused with pathologies (Smith et al 2012).…”
Section: Sample Structure Of the Reportmentioning
confidence: 99%